Summer variations : for viola and piano - Wessman, Harri, 1949-; Fennica Gehrman (Helsinki : Fennica Gehrman, 2024)
1 teos.
Osat: -- 1. Summer theme -- 2. What is this? -- 3. Pizzicato -- 4. Con sordino -- 5. Stile concitato ostinato -- 6. Tango -- 7. Finale.
Musiikin esityskokoonpano: alttoviulu, piano.
Kokonaisteos.
Ensiesitys: Yuri Gandelsman, alttoviulu & Risto Lauriala, piano, 15.6.1998.
Keywords: kesä; muunnelmat (musiikki); duot